Impact of magnesium supplementation on clinical outcome and disease progression of patients with diabetic nephropathy: a prospective randomized trial - Nihal Halawa; Tamer Wahid Elsaid; Lamia Mohamed El Wakeel; May Ahmed Shawki (SAGE Publishing, 2023)
Background: Magnesium (Mg) deficiency is closely linked with proteinuria. Objectives: To assess the impact of oral Mg citrate supplementation on the clinical outcome of diabetic nephropathy (DN) patients. Design: This was a prospective, randomized, controlled, open-label study. Methods: Sixty DN patients were recruited from Nephrology and Endocrinology departments, Ain Shams University Hospitals, Cairo, Egypt. Patients were assigned by stratified randomization based on their Mg status, to either Mg citrate group, ( n  = 30), who received the standard regimen + oral Mg citrate 2.25 g/day or Control group, ( n  = 30), who received the standard regimen only. The primary endpoint was a change in urinary albumin to creatinine ratio (UACR) after 12 weeks. Secondary outcomes were insulin resistance, glycemic control, lipid profile, serum osteocalcin, quality of life (QoL) and Mg tolerability. Results: Out of a total of 60 patients enrolled, only 54 patients (26 in Mg citrate group and 28 in the control group) completed the study. Groups were comparable at baseline. The UACR median percent reduction was significantly higher in the Mg citrate group (−6.87%) versus (−0.9%) in the Control group, p  = 0.001. After 12 weeks, the estimated glomerular filtration rate significantly improved in the Mg citrate group versus Control group ( p  = 0.001). Comparable change was observed in glycemic indices. Lipid profile significantly improved in the Mg citrate group versus Control group ( p  = 0.001). Serum osteocalcin levels significantly declined in the Mg citrate group ( p  = 0.001) versus control group. Regarding QoL, the total score and all domains significantly improved in the Mg citrate group compared to control. The Mg supplement was tolerable with only mild reported side effects that required no intervention. Conclusion: Oral Mg citrate supplementation improved microalbuminuria in DN patients. It also had favorable effects on serum osteocalcin, lipid profile and QoL with no reported major side effects. Trial registration: ClinicalTrials.gov identifier: NCT03824379.